Sequential and synchronized hypertonicity-induced activation of Rel-family transcription factors is required for osmoprotection in renal cells - Casali, Cecilia Irene (2018)
NF-κB and TonEBP belong to the Rel-superfamily of transcription factors. Several specific stimuli, including hypertonicity which is a key factor for renal physiology, are able to activate them. It has been reported that, after hypertonic challenge, NF-κB activity can be modulated by TonEBP, considered as the master regulator of transcriptional activity in the presence of changes in environmental tonicity. In the present work we evaluated whether hypertonicity-induced gene transcription mediated by p65/RelA and TonEBP occurs by an independent action of each transcription factor or by acting together. To do this, we evaluated the expression of their specific target genes and cyclooxygenase-2 (COX-2), a common target of both transcription factors, in the renal epithelial cell line Madin-Darby canine kidney (MDCK) subjected to hypertonic environment. The results herein indicate that hypertonicity activates the Rel-family transcription factors p65/RelA and TonEBP in MDCK cells, and that both are required for hypertonic induction of COX-2 and of their specific target genes. In addition, present data show that p65/RelA modulates TonEBP expression and both colocalize in nuclei of hypertonic cultures of MDCK cells. Thus, a sequential and synchronized action p65/RelA → TonEBP would be necessary for the expression of hypertonicity-induced protective genes.